Developmental evaluation of the healthy futures of Texas’ puberty curriculum: On My Way - Schormann, Elizabeth; Betori, Anthony; Neubauer, Leah C. (Frontiers in Public Health, 2024)
Background: This paper will describe a developmental evaluation of a pilot of a puberty curriculum that was implemented in grades four to six in San Antonio, Texas. The pilot evaluation assessed the initial feasibility and acceptability of curricular components. The developmental evaluation framework guided the questions in an ever-changing environment where new tools were created as the situation called for them (Dupuis et al. 2013).Methods: The evaluation team utilized purposive sampling methods, surveys, and facilitator notes to guide the collaborative process. Both Google and Microsoft platforms were used for analysis and collection of findings.Results: Facilitator notes and surveys revealed that while comfortable leading sessions, there were still issues in timing and student comprehension. From a student's point of view, while many (60%) reported feeling uncomfortable during lessons, a greater majority (80%) reported learning something from the sessions. Conclusion: Developmental evaluation was a crucial piece of the pilot sessions and revision process despite any limitations. A user-focused and adaptable evaluation generated greater opportunities for positive change within the curriculum and its delivery.